AB0009 Genetic association of mitochondrial dna polymorphisms with behÇet's disease in a korean population. (12th June 2018) - Kwon, M.-H.; Joung, C.-I.; Yoo, S.-J.; Kang, S.W.; Yoo, I.S.; Kim, J.; Choi, I.A.; Lim, M.-K.
Abstract : Background: Behcet's disease(BD) is an inflammatory multi-genetic disorder with unknown etiology. In the previous study, we sequenced whole mitochondrial nucleotides from blood of 20 BD patients and 10 sex-, age-matched healthy controls, m.248A>G, m.709G>A, m.3970C>T, m.6392T>C, m.6962G>A, m.10310G>A, m.10609T>C, m.12406G>A, m.12882C>T, m.13928G>C, m.16129G>A, and m16304T>C were more frequently observed in patients group than healthy control without statistical significance. While, m.304C>A, m.3010G>A, m.4883C>T, m.5178C>A, and m.14668C>T were more frequent in control group (p=0.008, 0.026, 0.007, 0.007, and 0.026, respectively). m.16182A>C, m.16183A>C, m.16189T>C were associated with uveitis (p=0.041, 0.022, and 0.014, respectively). Objectives: We performed a follow-up study to validate these possible associations in larger groups. Methods: Whole blood or buffy coat were collected from 98 BD patients from four university hospitals located in Chung-Cheong district of Republic of Korea, 196 age-, sex-matched healthy controls from Konyang University Hospital. Above mentioned 20 targeted mitochondrial DNA(mtDNA) genomes were analysed using MassARRAY ® system(Agena Bioscience, Inc., San Diego, CA, USA) for m.709, m.3010, m.4883, m.6392, m.6962, m.10310, m.10609, m.12406, m.12882, m.13928, and m.14668; Sanger sequencing for m.248, m.304, m.5178, m.16129, m.16182, m.16183, m.16189, and m.16304; and TaqMan-based genotyping assay(Applied Biosystems, Foster City, CA, USA) for m.3970. Results were compared with the revised Cambridge Reference Sequence (rCRS). Chi square or Fisher's exact test were used to analyse association of mtDNA alterations between groups and between mtDNA alterations and clinical/laboratory characteristics. Results: Presence of m.248A>G, m.304C>A, m.709G>A, m.3010G>A, m.3970C>T, m.4883C>T, m.5178C>A, m.6392T>C, m.6962G>A, m.10310G>A, m.10609T>C, m.12406G>A, m.12882C>T, m.13928G>C, m.14668C>T, m.16129G>A, and m16304T>C were not differentiated by the groups. However, m.16812A>C was more frequently observed in the patient group than control [22 (22.4%) vs. 24 (12.2%), p=0.061], and it was significantly associated with HLA-B51 positivity (p = 0.011), arthralgia (p=0.043) and methotrexate use (p=0.02), and was not associated with uveitis in the follow-up study. Among clinical and laboratory characteristics in BD patients, thrombosis was more frequently observed in male patients than female patients [7 (22.6%) vs. 0 (0%), p<0.001], and WBC counts were lower in female patients [3642.3±3413.6 vs. 5200.8±3912.7, p=0.048]. Conclusions: We performed a follow-up study to validate possible associations between BD and 20 mtDNA alterations. m.16812A>C could be associated with BD and its several clinical or laboratory characteristics a Korean population. References: [1] Xavier JM, Shafiee NM, Ghaderi F, Rosa A, Abdollahi BS, Nadji A, et al. Association of mitochondrial polymorphism m.709G>A with Behçet's disease. Ann Rheum Dis2011;70:1514–6. [2] Kwon MH, Joung CI. Genetic Associations of Mitochondrial DNA Polymorphisms with Behçet's Disease in a Korean Population: A Pilot Study. J Rheum Dis 2016;23(1):23–9. Acknowledgements: The current study was supported by the National Research Foundation of Korea funded by the Korean Government (grant no. NRF-2017R1C1B2008199). Disclosure of Interest: None declared